Is a “floater” always a floater? Case report and short review of sphenoid meningiomas’ ocular manifestation - Sokalski, Dominik; Szaflik, Jacek P.; Przybek-Skrzypecka, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2024)
Meningiomas are the most common primary brain tumours. The incidence of meningiomas increases progressively with age and might be related to general diseases, e.g. neurofibromatosis type 2 and exposure to radiation. Ocular symptoms are mainly reported in sphenoorbital meningiomas with proptosis, decreased visual acuity and visual field scotomas being the most common. Despite the fact that benign and slow-growing tumours with orbital extension predominate among meningiomas, early diagnosis increases the probability of safe neurosurgical removal and full visual recovery. Thus, healthcare professionals need to be aware of the symptoms of meningiomas for the proper differential diagnosis of potentially life- and sight-threatening diseases. We present a case report of a patient complaining of a black spot moving in front of her eye for 3 months, which was misdiagnosed as a floater. We aim to emphasize the proper history taking and ancillary testing scheme when the initial diagnosis is uncertain. Additionally, sphenoorbital meningiomas’ ocular symptoms, post-surgery follow-up regimen and risk factors for regrowth are reviewed.